Бабушкины сказки - Есенин Сергей Александрович (Книги - мои друзья, 2018)
Экземпляры: аб. Центральная библиотека (20190520) / Инвентарный номер: 6718 / Цена: / Сис.шифр: 84(2=411.2)6-5 / Авт.знак: Е 82 / ББК: 84(2=411.2)6-5